INTRODUCTION TO CRIMINOLOGY – SOC 515 - Rebellon, Cesar (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course aims to answer three primary questions. First, what is the nature and extent of crime in the United States and abroad? Second, what theories have criminologists devised to explain crime and what does the empirical evidence suggest about the relative merits of these theories? Third, how have policy makers attempted to control crime and how effective have these strategies proven?